Bioremediation of oil spills in soil - Al-Khatib, Ma'an Fahmi Rashid; Alam, Md. Zahangir; Husain, Iman A. F. (2010)
Oil spillage can cause a critical environmental impact on soil. Thus, many technologies have been developed for treating land contaminated by petroleum products. In this project, crude oil contaminated soil will be treated by bioremediation using oil-utilizing bacterial consortium. The bacterial consortium will be isolated from the crude-oil contaminated soil samples, and the best hydrocarbons degrading organisms will be selected for developing the bioremediation process. Water sludge with known composition will be used as nutrient source for the degradation process. The highest growth and hydrocarbon-degradation rate bacteria with the optimum process parameters will be used for the design of the bioremediation process.